The Giant Goldfish Robbery - "Kidd, Richard" (Penguin Random House Children's: UK, 2012)
An adventure story about a little boy who befriends an elderly gentleman who is a collector of Koi Carp, and how he unexpectedly tackles the burglars who try to steal the fish with the help of the school bully and several hundred alarm clocks.
Keywords: Action & Adventure